Analisis Implementasi Dari Akuntansi Penjualan Konsinyasi Berdasarkan PSAK No.72 Pada Toko Azzura Jaya Kosmetik - Tanti Pratiwi; Widya Febryari Anita (Jurnal Akuntansi dan Keuangan, 2023)
In a post-Covid-19 pandemic situation like this, every company definitely wants to maximize their business activities. In order for a company to survive in a competitive competitive position, a company is expected to be able to improve and maximize an effective strategy to increase sales in order to achieve success in product marketing activities. In addition, companies must also be able to find reliable partners to maximize sales. Lately, consignment sales have been in great demand by companies. This is because it will make it easier and profitable for the company to maximize its marketing activities. One of the objectives of this research is to find out whether the application of sales accounting on a consignment basis at the Azzura Jaya Cosmetics store is in accordance with PSAK 72 or not. This study uses a descriptive analysis method, because the contents of this research require visualization to be able to get facts with the right opinion regarding the application of consignment accounting at Azzura Jaya Cosmetics Store using separate and inseparable methods. For the results of this study, namely revenue in the 4th quarter (Q4) in 2021 (October, November and December) always increases, even though there are still some products left. The closer to the end of the year, it turns out that sales are increasing because usually people will shop for those needs or needs when the year's end is near. From the results of this study, Azzura Jaya Cosmetics should continue to try to develop a marketing network so that the sales of products from PT Jalur Mandiri Utama increase so that they can be sold out every month. And for the recording of the results of the sale of consignment goods implemented by PT Jalur Mandiri Utama it is in accordance with the concept in PSAK 72 in recording and also acknowledging it.